PENGARUH PENGGUNAAN LKPD BERBANTUAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KOMPETENSI KETERAMPILAN PESERTA DIDIK - yora florensia; Yurnetti Yurnetti; Hamdi Hamdi (PILLAR OF PHYSICS EDUCATION, 2018)
This research tries to apply student work sheet (LKPD) with the help of Problem Based Learning (PBL) which is expected to make the students active in learning so that their competence increases. The purpose of this research is to investigate the influence of LKPD of model PBL-assisted teaching on the competence of science students of grade 10th SMA N 9 Padang both on the aspects of knowledge, attitude, and skills. The type of research conducted is quasi experimental research with randomized control group only design. Sampling is done by using purposive sampling technique. Research instruments include final tests for knowledge competencies, observation sheets for attitude competencies and assessment rubrics for skills competencies. Data analysis was perform using statistical test. Based on the data analysis, the average value for experimental group and control group on knowledge competence are 74,25 and 63,18 attitude competencies are 84,38 and 80,04 and skill competence is 86,04 and 82,70. The difference data for all the competencies of the two sample classes is normally distributed and has a homogeneous variance, so that the two-tame equality test with t test is used. From the calculation the percentage of influence of LKPD-assisted PBL teaching model to students' Physic competence in knowledge 17.35 %, attitude 25.05% and skill 32.02%.